2017
DOI: 10.1111/jgs.14930
|View full text |Cite
|
Sign up to set email alerts
|

Opioids and Other Central Nervous System–Active Polypharmacy in Older Adults in the United States

Abstract: Background/Objectives Central Nervous System (CNS)-active medication polypharmacy, defined by the Beers Criteria as ≥3 CNS-active medications, poses significant risks for older adults. Among adults ages ≥65 seen in U.S. outpatient medical practice, we determined patterns and trends in contributions to CNS polypharmacy of each medication class. Design The National Ambulatory Medical Care Survey (2004–2013). Setting U.S. outpatient medical care. Participants Visits by older adults to outpatient physicians … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
48
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(49 citation statements)
references
References 22 publications
1
48
0
Order By: Relevance
“…However, increased drug use among frail individuals suggests a complex bidirectional relationship, most apparent in cross‐sectional analyses . Although clinical practice guidelines discourage co‐prescribing opioids and benzodiazepines due to the risks of dizziness, falls, dependence, respiratory depression, and death, this combination is often co‐prescribed and co‐used in the United States . Nonopioid analgesic and nonbenzodiazepine sedative‐hypnotics are also associated with increased risks of adverse events, geriatric syndromes, and death .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, increased drug use among frail individuals suggests a complex bidirectional relationship, most apparent in cross‐sectional analyses . Although clinical practice guidelines discourage co‐prescribing opioids and benzodiazepines due to the risks of dizziness, falls, dependence, respiratory depression, and death, this combination is often co‐prescribed and co‐used in the United States . Nonopioid analgesic and nonbenzodiazepine sedative‐hypnotics are also associated with increased risks of adverse events, geriatric syndromes, and death .…”
mentioning
confidence: 99%
“…24 Although clinical practice guidelines discourage co-prescribing opioids and benzodiazepines due to the risks of dizziness, falls, dependence, respiratory depression, and death, 26 this combination is often co-prescribed and co-used in the United States. 27 Nonopioid analgesic and nonbenzodiazepine sedative-hypnotics are also associated with increased risks of adverse events, geriatric syndromes, and death. 28 However, association analyses of prescription drug use for pain and for sleep and incident frailty have not been published.…”
mentioning
confidence: 99%
“…Unfortunately, other than the use of opioids, the contribution of individual therapeutic classes to CNS polypharmacy cannot be determined. Readers interested in learning more about this are referred to 2 additional publications by the same group of authors using the same data sources . Because of the nature of the data, the unit of analysis is not the percentage of the U.S. population of older adults with evidence of CNS polypharmacy but the percentage of outpatient visits.…”
Section: Resultsmentioning
confidence: 99%
“…Readers interested in learning more about this are referred to 2 additional publications by the same group of authors using the same data sources. 7,8 Because of the nature of the data, the unit of analysis is not the percentage of the U.S. population of older adults with evidence of CNS polypharmacy but the percentage of outpatient visits. A population-based cohort study reported that the 4.3% were taking 2 or more CNS active medications in 2002-03.…”
Section: Central Nervous System-active Polypharmacy In Older Adultsmentioning
confidence: 99%
“…24 NAMCS data are publicly available and widely used as a source for numerous assessments of medical care and prescribed medications in ambulatory settings in the US, including studies of psychiatric disorders and treatments. [25][26][27][28][29][30][31][32][33] The survey uses a stratified probability sampling procedure comprising multiple stages: first, selection by geographic area (eg, counties or county groups); second, within each geographic area by physician name, stratified by physician specialty; and third, by week, with each sampled physician randomly assigned to 1 of 52 weeks of data collection each year. 22,23 Finally, from each physician and week, a sample of office visits is chosen at random.…”
Section: Methodsmentioning
confidence: 99%